Carbon capture from natural gas using multi-walled CNTs based mixed matrix membranes - Hussain, A. (2019)
Most of the polymers and their blends, utilized in carbon capture membranes, are costly, but cellulose acetate (CA) being inexpensive is a lucrative choice. In this research, pure and mixed matrix membranes (MMMs) have been fabricated to capture carbon from natural gas. Polyethylene glycol (PEG) has been utilized in the fabrication of membranes to modify the chain flexibility of polymers. Multi-walled carbon nanotubes (MWCNTs) provide mechanical strength, thermal stability, an extra free path for CO2 molecules and augment CO2/CH4 selectivity. Membranes of pure CA, CA/PEG blend of different PEG concentrations (5, 10, 15) and CA/PEG/MWCNTs blend of 10 PEG with different MWCNTs concentrations (5, 10, 15) were prepared in acetone using solution casting techniques. Fabricated membranes were characterized using SEM, TGA and tensile testing. Permeation results revealed remarkable improvement in CO2/CH4 selectivity. In single gas experiments, CO2/CH4 selectivity is enhanced 8 times for pure membranes containing 10 PEG and 14 times for MMMs containing 10 MWCNTs. In mix gas experiments, the CO2/CH4 selectivity is increased 13 times for 10 PEG and 18 times for MMMs with 10 MWCNTs. Fabricated MMMs have a tensile strength of 13 MPa and are more thermally stable than CA membranes. Â© 2017, Â© 2017 Informa UK Limited, trading as Taylor & Francis Group.